2021
DOI: 10.1111/aos.14843
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in von Hippel‐Lindau disease

Abstract: Background/Aims: Retinal haemangioblastomas (RH) remain a major cause of visual impairment in patients with von Hippel-Lindau (VHL) disease. Identification of genotype-phenotype correlation is an important prerequisite for better management, treatment and prognosis. Methods: Retrospective, single-centre cohort study of 200 VHL patients. Genetic data and date of onset of RH, central nervous system haemangioblastomas (CNSH), pheochromocytoma/paraganglioma (PPGL), clear cell renal cell carcinoma (ccRCC) and pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…The onset age of CHB was also earlier than RCC, which is consistent with recent research. 25 In the previous study, the mean onset age was 31.2±12.8 years. We could conclude that the mean onset age was slightly earlier in affected offspring when compared with the whole VHL patients.…”
Section: Discussionmentioning
confidence: 85%
“…The onset age of CHB was also earlier than RCC, which is consistent with recent research. 25 In the previous study, the mean onset age was 31.2±12.8 years. We could conclude that the mean onset age was slightly earlier in affected offspring when compared with the whole VHL patients.…”
Section: Discussionmentioning
confidence: 85%
“…Another limitation is represented by the lack of genotype-phenotype correlations. Therefore, we cannot exclude that the genotype of VHL germline mutation may differently influence the microglia behavior in the retina [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In recent reviews, Michael Reich et al concluded the data from single-centre cohort study of Germany including 216 patients with clinically expected VHL disease due to positive family history or the presence of VHL typical tumors [ 44 ]. In total, 42 different rare VHL gene variants were detected, including truncating (Deletion, VHL gene deletion, Deletion Exon 1 and 2, Deletion Exon 2 and 3, Deletion Exon 1, Deletion Exon 2, Deletion Exon 3), Splice (c.464-2A > G), Frameshift (c.220del, c.408del, c.493del), Nonsense (c.394C > T, c.481C > T, c.490C > T, c.548C > A, c.555C > A), In frame (c.227_229del), Missense (c.233A > G, c.235C > G, c.238A > C, c.239G > T, c.254T > C, c.256C > G, c.257C > A, c.262T > A, c.266 T > C, c.269A > T, c.292 T > C, c.319C > G, c.320G > A, c.335A > G, c.386T > C, c.388G > A, c.395A > C, c.407T > C, c.461C > T, c.463G > C, c.475A > G, c.486C > G, c.491A > T, c.499C > T, c.562C > G), Synonymous (c.93G > A).…”
Section: Discussionmentioning
confidence: 99%